2022
DOI: 10.3390/microbiolres13040054
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Characterization of Nosocomial Carbapenem-Resistant Klebsiella pneumoniae Co-Harboring blaNDM and blaOXA-48 in Jeddah

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP)-associated infections have become a major concern and life-threatening worldwide. Understanding the epidemiology of CRKP using a reliable molecular technology can help to develop an effective infection control policies. In the western region of Saudi Arabia, there are no sufficient data on the prevalence of CRKP and its carbapenem-resistant determinants. Therefore, this study aimed to determine the molecular epidemiology of CRKP and identify the most common car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Furthermore, in Iraq; Haji et al [20] reported bla VIM gene to be the most prevalent gene detected and no bla KPC gene was found. Regarding Saudi Arabia, Alhazmi et al [27] found that bla OXA-48 gene was the most common gene detected, and consistent with our results all of their isolates were negative for the bla IMP gene.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in Iraq; Haji et al [20] reported bla VIM gene to be the most prevalent gene detected and no bla KPC gene was found. Regarding Saudi Arabia, Alhazmi et al [27] found that bla OXA-48 gene was the most common gene detected, and consistent with our results all of their isolates were negative for the bla IMP gene.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, no isolates exhibited positivity for the KPC production activity, as shown in Table 5 . The KPC enzyme is considered one of the non-dominant genes in the K. pneumoniae bacterium isolated in Saudi Arabia, which was previously monitored in studies conducted on wastewater [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, In Riyadh city, the antibiotic resistance profile of MDR-KP and the carbapenem MICs for most strains were 16 µg/mL [ 22 ]. Similarly, a recent report from Jeddah, Saudi Arabia, showed elevated MRP and IMIP MICs (above 16 g/mL) in CRE K. pneumonia isolates co-harbouring OXA-48 and New Delhi metallo-beta lactamase (NDM) carbapenemases [ 23 ]. However, the studies mentioned above targeted MDR-KP isolates (similar to our study), and not all K. pneumonia strains were received in the microbiological laboratory.…”
Section: Discussionmentioning
confidence: 99%